O legado de Georg Groddeck: genuinidade e originalidade - Silva, Maria Consuelo da Costa Oliveira e (2009)
Researches over psychosomatic theme point to various authors. Each one with their own definition of the theme. By consequence there is no consistent definition of it. It is from this point that the author will use Georg Groddeck as a central theme of this dissertation. Groddeck calls the attention on the subject to be easily announced as the father of psychosomatic besides the originality and uniqueness of his theories. The main objective of this paper is to make a deeper reading of Groddecks work, categorizing it, emphasizing his intellectual production, giving it biographic context and enhancing his procedures to understand the historical context of his time. This work aim to subtract the concepts of psychosomatics found on Groddecks work before his contacts with Freud and psycanalisis passing by his biography and writings that approach the first world war. Sources are mainly primary ones